Generalized prejudice reduction: Speciesism, sexism and racism - What if we can diminish all by tackling just one? - Pajovic, D.; Rodrigues, R. B. (Journal for Critical Animal Studies, 2023)
There is a history of analysis of relationships between different prejudices, including the interconnection of racism, sexism, and speciesism. Likewise, several studies suggested that prejudices have the same underlying causes and assumptions, one of the most significant being Social Dominance Orientation (SDO), or belief in the legitimacy and desirability of hierarchies. Therefore, if prejudices have a common root (in SDO), tackling just one of them should result in spillover prejudice reduction effect to all the others via a reduction in SDO. The current study examined this idea by testing the effect of an intervention design to reduce prejudices towards women, black people, and non-human animals, and testing SDO as a mediator. Participants were randomly assigned to one of four conditions (speciesism, sexism, racism, or control) where they underwent a prejudice reduction intervention as an elaborative imagined contact induction. The participants expressed strong intercorrelations between the SDO, sexism, racism and speciesism attitudes. However, interventions proved to be statistically nonsignificant, alongside the mediation of SDO. The limitations of the study are discussed and directions for future studies are provided.